Internalisasi Kearifan Lokal Sebagai Upaya Pelestarian Adat dan Budaya Masyarakat Dayak Kiyu Desa Hinas Kiri Kabupaten Hulu Sungai Tengah - Rifani, Muhammad; Damaiyanti, Varinia Pura; Khotimah , Usnul; Rasidah, Miftah; Pratama, Muhammad Daffa'; Permadani, Muhammad Bagus; Rahma SAS, Cindi Novita; Huda, Nurul; Hawa, Siti; Rahmadini, Nasifa Noor; Koso, Difa Salsabila (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Local wisdom is an identity that reflects the unique values and traditions of the local community. Hinas Kiri Village, which is inhabited by the Dayak Meratus community, has local wisdom that is very important to maintain a balance between modernization and cultural preservation. These values are reflected in the lifestyle that continues to be applied by the community and upholds ancestral culture to this day. This service aims to internalize local wisdom as part of efforts to preserve customs and culture, especially in the Dayak Kiyu community. Thus, visitors can also enjoy seeing and interacting directly with local culture. Therefore, the service team wanted to dig deeper into the local wisdom of the Dayak Community from Hinas Kiri Village. The program implementation is obtained through the following stages, namely; 1) Focus group discussion; 2) Nature school; 3) Village discussion; and 4) Internalization of local wisdom. The method used in this service activity is the live-in method, where researchers live and interact directly with the community. The results of this effort are expected to be a means of preserving traditional culture in Hinas Kiri Village. So that the benefits are not only felt by the local community, but also by tourists. This program is also expected to strengthen public awareness of the importance of local wisdom and its role in encouraging sustainable tourism. Through this program, the service team believes that tourism developed by the Dayak Kiyu Community through its local wisdom can make Hinas Kiri Village superior in terms of promoting cultural tourism while maintaining the typical cultural heritage of Dayak Meratus.